Deforming buccal habits in children between 5 and 11 years old in Cienfuegos. 2005. - Odalys Acevedo Sierra; Clara Rosa Rosell Silva; Clotilde Mora Pérez; Elsie María Padilla Gómez (Medisur)
Background: Habits are very complex neuromuscular patterns. Deforming buccal habits can obstruct the normal growth and development of stomatognathic system. Objective: To characterize subjects with deforming habits. Method: An observational, descriptive and correlacional study was developed in 341 children between 5 and 11 years old in Cienfuegos from December 2004 to September 2005. In addition to the clinical examination, an interview was performed to parents/tutors and teachers. Data was collected in a data formulary and variables as age, sex, deforming buccal habits and dentomaxillofacial anomalies were analyzed. Findings: Deforming buccal habits frequency was 79%. The most common habits were lingual protraction (47, 2%), baby bottle suction (32, 6%) and onychophagia (23, 5%), all of them predominant in girls. 75% of the children with these habits developed anomalies; being vestibule-version (21, 1%), increased over bite (20,2%) and bilabial incompetence (17,9%) the most frequent. Conclusions: It was confirmed that deforming Buccal habits are a health problem that affects the stomatognathic system. This should be treated by the General Integral Dentist in a systematic and direct way.